Electrical Vestibular Stimulation after Vestibular Deafferentation and in Vestibular Schwannoma - Aw, Swee Tin; Todd, Michael John; Lehnen, Nadine; Aw, Grace Elizabeth; Weber, Konrad Peter; Eggert, Thomas; Halmagyi, Gabor Michael (PloS one, 2013)
Vestibular reflexes, evoked by human electrical (galvanic) vestibular stimulation (EVS), are utilized to assess vestibular function and investigate its pathways. Our study aimed to investigate the electrically-evoked vestibulo-ocular reflex (eVOR) output after bilateral and unilateral vestibular deafferentations to determine the characteristics for interpreting unilateral lesions such as vestibular schwannomas. EVOR was recorded with dual-search coils as binocular three-dimensional eye movements evoked by bipolar 100 ms-step at EVS intensities of [0.9, 2.5, 5.0, 7.5, 10.0] mA and unipolar 100 ms-step at 5 mA EVS intensity. Five bilateral vestibular deafferented (BVD), 12 unilateral vestibular deafferented (UVD), four unilateral vestibular schwannoma (UVS) patients and 17 healthy subjects were tested with bipolar EVS, and five UVDs with unipolar EVS. After BVD, bipolar EVS elicited no eVOR. After UVD, bipolar EVS of one functioning ear elicited bidirectional, excitatory eVOR to cathodal EVS with 9 ms latency and inhibitory eVOR to anodal EVS, opposite in direction, at half the amplitude with 12 ms latency, exhibiting an excitatory-inhibitory asymmetry. The eVOR patterns from UVS were consistent with responses from UVD confirming the vestibular loss on the lesion side. Unexpectedly, unipolar EVS of the UVD ear, instead of absent response, evoked one-third the bipolar eVOR while unipolar EVS of the functioning ear evoked half the bipolar response. The bidirectional eVOR evoked by bipolar EVS from UVD with an excitatory-inhibitory asymmetry and the 3 ms latency difference between normal and lesion side may be useful for detecting vestibular lesions such as UVS. We suggest that current spread could account for the small eVOR to 5 mA unipolar EVS of the UVD ear.